Lantern City Vol. 1. - Crafts, Trevor (Lantern City., 2016)
What's to Love: From the writings of Jules Verne and H.G. Wells, to comics like The League of Extraordinary Gentlemen, and Lady Mechanika, the detailed and imagination-fueled steampunk movement has excited fans worldwide. Lantern City explores everything we love about the genre and what it takes to change a person's place in the world. Created by Trevor Crafts, Bruce Boxleitner, and Matthew Daley, written by Daley, Paul Jenkins (Fairy Quest), and Mairghread Scott (Transformers), and illustrated by Carlos Magno (RoboCop), Lantern City explores what it takes to change a person's place in the wo.